The Analysis ofProtection and Fulfillment The Rights of Persons With Disabilities in Gunungkidul District of Yogyakarta province - Dr. Ami Surwanti, M.Si. (Fakultas Ekonomi - UMY, 2016)
The Analysis ofProtection and Fulfillment The Rights of Persons With Disabilities in Gunugkidul District of Yogyakarta Province The 2016 Intemational Conference Of Management Sciences 978-602-7 577-63-3 March 2016 Fakultas Ekonomi - UMY